2023
DOI: 10.3389/fonc.2022.999894
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the clinicopathological characteristics and prognosis of triple-positive breast cancer and HER2-positive breast cancer—A retrospective study

Abstract: BackgroundAdjuvant chemotherapy and targeted therapy have become standard postoperative therapeutic modalities for human epidermal growth factor receptor 2 (HER2)-positive breast cancer(HER2-positive,HR-negative), including triple-positive breast cancer(HER2-positive,HR-positive). However, these two types of breast cancer differ in terms of pathogenesis. This article analyzes these two types of breast cancer by comparing their prognoses.MethodsThe clinicopathological characteristics of 135 patients, including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…In the analysis of prognostic factors, we also found that patients whose breast cancer was not the first primary malignancy tended to have a poorer prognosis, which is also true in other cancers (34)(35)(36). In general, higher number of positive lymph nodes and lymph node metastasis rate are associated with poor prognosis of breast cancer patients (37)(38)(39). For IMPC patients, a literature (15) shows through univariate analysis that IMPC patients with ≥4 positive lymph nodes have shorter OS compared to lymph node negative patients, while the OS of IMPC patients with 1-3 positive lymph nodes is similar to that of patients with lymph node negative diseases.…”
mentioning
confidence: 61%
“…In the analysis of prognostic factors, we also found that patients whose breast cancer was not the first primary malignancy tended to have a poorer prognosis, which is also true in other cancers (34)(35)(36). In general, higher number of positive lymph nodes and lymph node metastasis rate are associated with poor prognosis of breast cancer patients (37)(38)(39). For IMPC patients, a literature (15) shows through univariate analysis that IMPC patients with ≥4 positive lymph nodes have shorter OS compared to lymph node negative patients, while the OS of IMPC patients with 1-3 positive lymph nodes is similar to that of patients with lymph node negative diseases.…”
mentioning
confidence: 61%
“…4 Several studies have consistently shown that TPBC is highly invasive and exhibits increased proliferative activity. 5,6 TPBC patients generally present with higher tumor grades, larger tumor sizes, and an elevated risk of lymph node metastases. 5 There have been few studies on patients with TPBC, particularly for those at advanced stage disease.…”
Section: Introductionmentioning
confidence: 99%
“…TPBC has been classified as an independent biological subtype, with a poorer prognosis compared to HR‐positive (HR+)/HER2‐negative (HER2‐) subtype but a better prognosis than HR‐negative (HR‐)/HER2‐positive (HER2+) subtype 4 . Several studies have consistently shown that TPBC is highly invasive and exhibits increased proliferative activity 5,6 . TPBC patients generally present with higher tumor grades, larger tumor sizes, and an elevated risk of lymph node metastases 5 …”
Section: Introductionmentioning
confidence: 99%